ILLOCUTIONARY ACTS BY LARA JEAN’S UTTERANCES IN TO ALL THE BOYS MOVIE TRILOGY - Karimatul Auliya (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2022)
This research aimed to describe and classify types of illocutionary acts found in Lara Jean's utterances in To All the Boys movie trilogy including To All the Boys I’ve Loved Before (2018), To All the Boys P.S I Still Love You (2020), and To All the Boys Always and Forever (2021). The research method used in this research was descriptive qualitative research, where the primary data were in the form of transcripts of Lara Jean's utterances. The data were elicited through documentation, namely gathering the data and identifying the linguistic units according to the pragmatics study. In analyzing the data, the researcher utilized the theory of Speech Acts by Austin (1962) and the classification of the types of illocutionary acts by Searle (1979). The results showed five types of illocutionary acts found in Lara Jean's utterances in To All the Boys movie trilogy, such as assertives, directives, declaratives, expressives, and comisives. The researcher found 127 data in the three movies comprising  32 assertives,  37 directives,  5 commissives,  48 expressives, and  5 declaratives. The study revealed that the dominant use of illocutionary acts by Lara Jean in her utterances are expressives. The researcher concluded that in the movie trilogy, Lara Jean used expressive illocutionary acts to express her feelings to thank, apologize, praise, or state something in her mind. Key words: Pragmatics,Speech acts, Illocutionary acts, Function, Movie Trilogy